Razorpay : providing payment convenience to disruptors - Mukhopadhyay, Sandip; Mukherjee, Saral; Ganjoo, Divya (London : Indian Institute of Management, Ahmedabad, 2019)
Razorpay is a four-year-old Indian B2B Fintech startup in digital payments which is venturing into digital lending. It aims to simplify digital payment flows involved in the acceptance, processing and disbursement of payments through superior technology and automation. This case details how Razorpay creates value for businesses by offering service convenience in the B2B space. Razorpay started as a payment solutions provider, primarily known for its payment gateway.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Digital currency -- India; Electronic funds transfers -- India; Loans -- India; Finance -- Technological innovation -- Case studies